Studies on the genus Aporcelaimellus Heyns, 1965 (Nematoda, Dorylaimida, Aporcelaimidae). Four typical species with simple uterus from Southern Iberian Peninsula - Álvarez-Ortega, Sergio; Abolafia, Joaquín; Peña-Santiago, Reyes (Zootaxa, 2013)
Three new and one known species of the genus Aporcelaimellus with simple uterus and typical caudal region, mainly col-lected in natural areas of southeastern Iberian Peninsula, are studied, including descriptions, measurements, line illustra-tions and LM pictures. Aporcelaimellus baeticus sp. n. is characterized by a body length of 1.96–2.95 mm, lip region offset by constriction and 17–20 μm broad, odontostyle 17–22 μm long, neck 510–635 μm long, pharyngeal expansion 250–335 μm long, a dorsal cell mass at level of anterior end of intestine, uterus 60–150 μm long or 0.9–1.7 times the corresponding body diameter, vulva transverse (V = 48–54), tail convex conoid with broadly rounded terminus (30–46 μm, c = 47–80, c’ = 0.7–1.1), spicules 99–103 μm long, and 18–21 irregularly spaced ventromedian supplements which lack hiatus. Apor-celaimellus brevicaudatus sp. n. is characterized by a body length of 1.54–2.14 mm long, lip region offset by a more or less distinct constriction and 14–16 μm broad, odontostyle 13–15 μm long, neck 512 μm long, pharyngeal expansion 255 μm long, uterus 39–57 μm long or 0.9–1.0 times the corresponding body diameter, V = 50–55, tail short and rounded to hemispherical (24–27 μm, c = 66–82, c’ = 0.6–0.7) with inner core hardly reaching the middle of tail length, and male unknown. Aporcelaimellus rotundus sp. n. is characterized by its body 2.01–2.58 mm long, lip region offset by constriction and 19–20 μm broad, odontostyle 22–23 μm long, neck 455–579 μm long, pharyngeal expansion 226–316 μm long, a dis-tinct dorsal cell mass present at cardia level, uterus 28–74 μm long or 0.5–0.9 times the corresponding body diameter, V = 47–52, female tail short and conoid to rounded (27–33 μm, c = 64–90, c’ = 0.7–0.9), and males unknown. New data, including SEM pictures, sequences and taxonomic comments, are provided for A. waenga.